Sistem Proporsional Terbuka Bukan Akar Politik Uang Dalam Pemilu - Adrianto Adrianto; Achmad Musyaddad; Rini Admiwati; Wahyu Muharomdoni; Adji Suradji Muhammad (Pusat Riset dan Inovasi Nasional, 2025)
The influence of an open proportional representation system with a majority vote does not explain the rise of money politics and political corruption after the election period. Systemically, the influence of the electoral system is aimed more at establishing a stable party system and modeling coalition models to produce a model of political balance in managing relations between the Government and Parliament. Meanwhile, the quality of the implementation of the electoral system is actually determined by the quality of the institutionalization of political parties, including the tendency of the type of party. Money politics is the result of the poor quality of political institutions in a type of party that only focuses on electoral interests.